Family support modifies the effect of changes to same-sex marriage legislation on LGB mental health: evidence from a UK cohort study. (27th August 2021) - Teo, Celine; Metheny, Nicholas; Chum, Antony
Abstract: Background: Many lesbian, gay and bisexual (LGB) individuals continue to experience unique challenges, such as the lack of family support and access to same-sex marriage. This study examines the effect of the introduction of same-sex marriage in the UK (2013–14) on mental health functioning among sexual minorities, and investigates whether low family support may hamper the positive effects of marriage equality legislation among LGB individuals. Methods: This analysis included LGB participants ( n = 2172) from the UK household longitudinal study waves 3–7, comprising two waves before and two waves after marriage equality legislation passed in England, Wales and Scotland. Individual-level mental health functioning was measured using the mental component score (MCS-12) of the Short Form-12 survey. Fixed-effect panel linear models examined the effect of marriage equality on MCS-12 across varying family support levels. Analyses included adjustment for covariates and survey weights. Results: Legalization of same-sex marriage was independently associated with an increase of 1.17 [95% confidence interval (CI): 0.28–2.05] MCS-12 in men and 1.13 (95% CI: 0.47–2.27) MCS-12 in women. For men, each additional standard deviation of family support modified the effect of legalization on mental health functioning by +0.70 (95% CI: 0.22–1.18) MCS-12 score. No interaction was found in women. Conclusions: Our findings provide evidence that same-sex marriage will likely improve LGB mental health functioning, and these effects may be generalizable to other European countries. Since male sexual minorities with low family support benefited the least, additional interventions aimed at improving family support and acceptance of this group is required to help reduce mental health disparities.